Community Service Through Training and Mentoring “Traditional Herbal Recipes for Pregnancy and Postnatal Care” - Wibowo, Teguh Setiawan; Aswitami, Ni Gusti Ayu Pramita; Udayani, Ni Putu Mirah Yunita; Martini, Ni Made Dwi Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this training activity is to reduce the risk of Maternal Mortality Rate in the pregnant and postpartum women, provide more economical alternative methods, and increase the professional competence of midwives in pregnancy and postnatal care. The methods used are online presentations, questions/answers, and discussions via Zoom webinars as well as online and offline mentoring. The results w ere the community service activities through training on traditional herbal recipes for pregnancy and postpartum care received a positive response and were quite well received by the participants who took part in the training organized by the collaboration between the Future Insight Training Institute and STIKES Bina U sada Bali. It is hoped that there will be more in-depth collaboration between interested parties, such as carrying out follow-up projects from training with companies that have expertise in traditional medicines such as project partners.